Figurações do negro nas poesias de Cuti - Maia, Renata Felício (2019)
This dissertation aims to reflect on aspects related to black identity in Brazil, based on the interpretation of texts by the writer and teacher Luiz Silva (Cuti). The strategy adopted in this work aims to analyze works by the author, dealing concomitantly with the process of construction and legitimation of his literature. Emphasis is placed here on the writings concerning the imposition of respect for the African cultural heritage. The reflection on the black, the creative and research capacity makes the literary work of Cuti put it among the great writers of Brazil. He created a work that acts as a catalyst for important aspects of the African matrix culture heritage, serving as reference for Black - Brazilian literature. In the present work we present some reflections on the influence of social markers on the social representation of black. We discuss the consequences of these social constructors around the "black body" and the construction of their memory, as well as their implications for the construction of black identity in Brazil. In addition, we point to the importance of the actions of the black movement to the educational field in the struggle and conquest of public policies, such as law n. 10,639 / 03. From this perspective, we discuss the contribution of education to the deconstruction of stereotypes, as well as the importance of Afro Brazilians in the creation of possibilities for intervention in the process of identity formation, so that the dominant narratives about "being black" and "black body" are challenged and construct an educational space of resonance to stories and identities marginalized or not, but addressing the identities that the blacks bring in their family heirs and their ancestors, in opposition to the hegemonies and dogmas of some religions that do not respect the inheritances of African tradition.